Involvement of Mutation in ampD I, mrcA, and at Least One Additional Gene in β-Lactamase Hyperproduction in Stenotrophomonas maltophilia - Talfan, Asmaa (American Society for Microbiology, 2013)
It has been reported that targeted disruption of ampD I or mrcA causes β-lactamase hyperproduction in Stenotrophomonas maltophilia. We show here that β-lactamase-hyperproducing laboratory selected mutants and clinical isolates can have wild-type ampD I and mrcA genes, implicating mutation of at least one additional gene in this phenotype. The involvement of mutations at multiple loci in the activation of β-lactamase production in S. maltophilia reveals that there are significant deviations from the enterobacterial paradigm of AmpR-mediated control of β-lactamase induction. We do show, however, that S. maltophilia ampD I can complement a mutation in Escherichia coli ampD. This suggests that an anhydromuropeptide degradation product of peptidoglycan is used to activate AmpR in S. maltophilia, as is also the case in enteric bacteria.